Suplementação no período das águas de bovinos e bubalinos recriados em pastagem de capim-xaraés (Urochloa brizantha Syn. Brachiaria brizantha cv. Xaraés) - Silva, Daiane Cristina Marques da [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The objective of this study was evaluate the supplementation method of 20 beef cattle [Nelore; 10 + 1 month of age and 220 + 33kg body weight (BW)] and 20 buffaloes [Murrah water buffalo, 10 + 1 month of age and 206 + 29kg body weight (BW)] growing in (Urochloa brizantha cv. Xaraés) receiving supplementation (0.6% BW), or not (control). Animals were divided in two treatment groups (n = 10 animals of each genetic group for each treatment). Body weight were conducted at the beginning of the experiment (0d) and 28, 56 and 84 day, to determining weight gain (WG), average daily gain (ADG), and blood samples for determination of glucose. Hip height measurements (HH), body condition score (BCS), rib eye area (REA), backfat thickness - 12th rib (BF), rump fat thickness (RFT) were determined at the beginning (0d) and the end (84d) of the study. The evaluation of feeding behavior was conducted (trough time, rumination, idleness and water intake) considering the time spent on each event. Cost of different treatments was calculated. There was no interaction between species and treatment.The beef cattle had higher values (P <0.01) of BW0d, BW28d, BW56d, BW84d, WGtotal, ADG28d, ADG56d, ADG84d, ADGtotal, HH0d, HH84d, REA84d (P = 0.04), total cost/head (P = 0.03) and income/head/ha when compared to buffaloes. Buffaloes had higher values (P < 0.01) of BCS0d, BCS84d, BF0d, BF84d, RFT0d, RFT84d, length of stay in the trough, water intake, and percentage supplement intake compared to beef cattle. Effect of treatment was detected (P < 0.01) for BW0d, BW28d, BW56d, BW84d, WGtotal, ADG28d, ADG56d, ADG84d, ADGtotal, BCS84d, REA84d, total cost/head, gain/@, income/head where supplemented animals showed higher values when compared to control animals. In conclusion, bovine genetic group excelled for weight gains while consuming a smaller proportion of ...

Objetivou-se com esse estudo avaliar o método de suplementação de 20 bovinos [(Nelore; 10 + 1 mês de idade e 220 + 33kg de peso vivo (PV) iniciais] e 20 bubalinos [Murrah; 10 + 1 mês de idade e 206 + 29kg (PV) iniciais] recriados em pasto de Urochloa brizantha cv. Xaraés, suplementados (0,6% PV) ou não (controle). Foram realizadas pesagens dos animais no início do estudo (0d) e nos dias 28, 56 e 84, para o cálculo do ganho de peso (GP), ganho médio diário (GMD), e coletas de amostras de sangue para determinação da glicose plasmática. Medidas da altura de garupa (AG), escore de condição corporal (ECC), área de olho de lombo (AOL), espessura de gordura subcutânea (EGS; 12a costela) e espessura de gordura da garupa (EGG) foram determinadas no início (0d) e no final (84d) do estudo. Foi realizada avaliação do comportamento ingestivo (tempo no cocho, ruminação, ócio e ingestão de água) considerando o tempo dispendido com cada evento. Custos dos diferentes tratamentos foram calculados. Não houve interação entre espécie e tratamento. Os bovinos apresentaram valores superiores (P < 0,01) de PV0d, PV28d, PV56d, PV84d, GPtotal, GMD28d, GMD56d, GMD84d, GMDtotal, AG0d, AG84d, AOL84d (P = 0,04), custo total/cabeça (P = 0,03) e lucro/cabeça/ha, quando comparados aos bubalinos. Enquanto que maiores valores (P < 0,01) de ECC0d, ECC84d, EGS0d, EGS84d, EGG0d, EGG84d, tempo de permanência no cocho, quantidade de água ingerida (P < 0,01), e consumo percentual de suplemento foram atribuídos aos bubalinos. Foi detectado efeito do tratamento (P < 0,01) para as características de PV0d, PV28d, PV56d, PV84d, GPtotal, GMD28d, GMD56d, GMD84d, GMDtotal, ECC84d, AOL84d, custo total/cabeça, ganho/@, receita/cabeça, para as quais os animais suplementados apresentaram maiores valores quando comparados aos animais controle. Conclui-se que o grupo genético bovino se destacou quanto aos ganhos de ...
Supplementation of growing beef cattle and buffaloes grazing xaraés-pasture (Urochloa brizantha Syn. Brachiaria brizantha cv. Xaraés) during rainy season
Keywords: Bovino - Alimentação e rações; Bufalo - Alimentação e rações; Pastejo rotativo; Chuvas; Viabilidade economica; Cattle Feeding and feeds